The SLIM1 transcription factor affects sugar signaling during sulfur deficiency in Arabidopsis. (13th September 2022) - Wawrzyńska, Anna; Piotrowska, Justyna; Apodiakou, Anastasia; Brückner, Franziska; Hoefgen, Rainer; Sirko, Agnieszka
Abstract: The homeostasis of major macronutrient metabolism needs to be tightly regulated, especially when the availability of one or more nutrients fluctuates in the environment. Both sulfur metabolism and glucose signaling are important processes throughout plant growth and development, as well as during stress responses. Still, very little is known about how these processes affect each other, although they are positively connected. Here, we showed in Arabidopsis that the crucial transcription factor of sulfur metabolism, SLIM1, is involved in glucose signaling during shortage of sulfur. The germination rate of the slim1_KO mutant was severely affected by high glucose and osmotic stress. The expression of SLIM1-dependent genes in sulfur deficiency appeared to be additionally induced by a high concentration of either mannitol or glucose, but also by sucrose, which is not only the source of glucose but another signaling molecule. Additionally, SLIM1 affects PAP1 expression during sulfur deficiency by directly binding to its promoter. The lack of PAP1 induction in such conditions leads to much lower anthocyanin production. Taken together, our results indicate that SLIM1 is involved in the glucose response by modulating sulfur metabolism and directly controlling PAP1 expression in Arabidopsis during sulfur deficiency stress. Abstract : During sulfur deficiency, the SLIM1 transcription factor directly and positively regulates PAP1 / MYB75 expression to induce sucrose-dependent anthocyanin biosynthesis, and hexokinase1 participates in signaling glucose levels through SLIM1 to transcriptional machinery.